2019
DOI: 10.1002/adbi.201800247
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Toxicity Assessment of Hybrid Diatomite Nanovectors Using Hydra vulgaris as a Model System

Abstract: sulfuric acid, hydrogen peroxide, hydrochloride acid, ammonium hydroxide, and hydrofluoric acid). [4] Recent research proposed natural nanostructured silica from diatomite as a valid alternative to synthetic porous silica. [5] Diatomite is a fossil material, produced in tons by mining industry. Diatomite structure, mainly made of hydrated amorphous silica, exhibits a porous morphology with a relatively high specific surface area (30.92 m 2 g −1 ). [6] In the last years, porous micro-and nanoparticles obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
13
0
1
Order By: Relevance
“…A, General scheme for toxicity score attribution according to Wilby's criterion (adapted from Reference [40]). B, Evaluation of toxicity of hPSiNPs and hPSiNPs‐PLL (in the latter case at different concentrations in order to establish the working conditions) at 2 hour incubation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A, General scheme for toxicity score attribution according to Wilby's criterion (adapted from Reference [40]). B, Evaluation of toxicity of hPSiNPs and hPSiNPs‐PLL (in the latter case at different concentrations in order to establish the working conditions) at 2 hour incubation.…”
Section: Resultsmentioning
confidence: 99%
“…A nerve net throughout the body constitutes a simple nervous system [37]. Hydra is sensitive to a range of pollutants and has been used as a biological indicator of water pollution [38] as well as target for biocompatibility studies of functional nanomaterials [39,40]. The toxicity of a substance can be measured and quantified by monitoring the animal morphology over time and following a criterion given by Wilby's classification, which attributes to Hydra a score from 10 to 0 (from elongated tentacles and body to disintegrated appearance [41]) according to the degree of harmfulness.…”
Section: Morphological and Optical Properties Of Hpsinps-pllmentioning
confidence: 99%
“…While surface coating with diatoms plays a crucial role in tissue integration, it was soon recognized that natural biosilica from diatoms also offers a promising biocompatible material for medicinal applications. In early 2019, Terracciano et al reported the in vivo compatibility and non-toxicity of diatom nanoparticles using a small invertebrate, the cnidarian freshwater polyp Hydra vulgaris , as an animal model [45]. Hydra polyps are highly sensitive to both organic and inorganic pollutants in their environment, leading in most cases to delayed growth, morphological changes, induction of apoptosis, and even alteration of gene expression [46,47].…”
Section: Diatoms As a Natural Biocompatible Materials For Therapeutmentioning
confidence: 99%
“…Moreover, just like the porous silicon, the diatom frustules have remarkable optical properties that change on exposure to chemical substances [8,9,10,11,12,13,14,15,16]; their surface can be functionalized [17], and in conclusion, the diatom frustules have been considered as bio-derived transducers for biosensing applications [18]. In the last years, due to their unique characteristics, an increasing enthusiasm about the use of diatoms in nanotechnology has been registered in many important fields, from nanomedicine to environment monitoring [19,20,21,22,23,24,25,26,27,28,29,30,31]. Two books have been recently published in the area of diatoms, fixing the state of art in emerging applications [32,33].…”
Section: Introductionmentioning
confidence: 99%